Innovative methodology for the development of operational management standards in the hotel business - Titomir, Ludmila; Kharenko, Dmytro; Markovska, Anastasiia (My University, 2023)
The object of the study is the role of corporate standards in increasing the effectiveness of service quality management in the hotel sector. The work is aimed at clarifying and expanding the theoretical and methodological provisions of service quality management in the field of hospitality, for which it is necessary to propose a toolkit for the development and implementation of corporate standards, and to develop recommendations for improving the effectiveness of service quality management. In the course of the study, logical approaches to the analysis and development of ways to improve the efficiency of service quality management in the field of hospitality based on corporate standards were used. The work specifies the terminological apparatus, substantiates the role and relevance of corporate standards in hotel service. The goals, tasks, functions and structure of corporate standards are analyzed. The types and distinctive features of corporate standards are established. The prerequisites for the wide application of standards in the field of hospitality are substantiated, in particular, the close connection of the quality of service with the work of the staff, the wide application of the chain form of the organization of the hotel business, the 24-hour mode of operation of hotel enterprises, the high role of operational management and high staff turnover. A toolkit for the development and implementation of corporate standards is proposed. The role of the process approach in the development of service standards is substantiated. A list of service standards for a hotel enterprise is proposed. Recommendations for improving the efficiency of service quality management based on corporate standards in the field of hospitality have been developed. A conclusion was made about the high role and effectiveness of using corporate standards as a service management tool in the field of hospitality. Mechanisms for the introduction and implementation of corporate standards have been developed. It is also important, that the list of standards of operational procedures becomes the basis for evaluating the results of the staff’s activities, which plays a role in the motivational programs of the hotel enterprise.
Kharenko Dmytro Innovative methodology for the development of operational management standards in the hotel business / Dmytro Kharenko, Ludmila Titomir, Anastasiia Markovskа // Technology Audit and Production Reserves. – 2023. – 1/4 (69). - С. 36-41. DOI: 10.15587/2706-5448.2023.275353
Keywords: operational standards; corporate standards; service standards; quality standards; hotel management; hotel service